2005
DOI: 10.1038/nbt1005-1315a
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: Design of a genome-wide siRNA library using an artificial neural network

Abstract: On page 1,000, in the last Methods section, line 4 from bottom of page, "HeLa cells were treated with 100 mM Deferoxamine Mesylate" should have read "HeLa cells were treated with 100 µM Deferoxamine Mesylate." In the supplementary online information, the original Supplementary Table 3 erroneously showed the Biopred algorithm scores (predicted relative activity) in the last column, instead of experimentally determined 'Normalized inhibitory activity'. This has been corrected in the new Supplementary Table 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The 2431 siRNAs of length 21 nucleotides with complete base pairing to their respective target sequences from a siRNA study were used as the empirical activity data to study [18] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…The 2431 siRNAs of length 21 nucleotides with complete base pairing to their respective target sequences from a siRNA study were used as the empirical activity data to study [18] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies [5,9,10] showed that the percentage of the GC content of the siRNA play an important role in its efficiency. In Figure 3 the average GC contents of the siRNA were calculated for the three groups (high efficient, moderate efficient and low efficient), which are equals (8.8, 10, 10.9 nt/19 nt of the AS strand) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Dataset 2431 was from [23], the 21-mer sequence and activity data used was from the corrigendum [44]. Dataset 579 was from the compiled 581 19-mer sequences and activities dataset used by [25], with the exception of five sequences that did not precisely correspond to their target gene DNA sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Two datasets are used in the present study. The first is a set of 2431 siRNA sequences of 21 nucleotides in length from [23], specifically from the corrigendum [44], referred to as dataset 2431 . The second is a compiled set of 579 siRNA sequences of 19 nucleotides in length from [25] referred to as dataset 579 .…”
Section: Introductionmentioning
confidence: 99%